Management of breast cancer patients leptomeningeal carcinomatosis: experience with Ommaya catheter - de Lacerda Pereira, Felipe; Assad Maia Sandoval, Letícia; Bernardes Ferreira, Luiza; Teixeira Leite, Ana Paula; Moreira Batista, Juliana; Strava Corrêa, Tatiana (Brazilian Journal of Case Reports, 2021)
Leptomeningeal Carcinomatosis is a recurrent complication in different types of tumors with systemic involvement, especially breast cancers. Thus, given the different forms of treatment for this disease, this article presents the effectiveness of using Ommaya catheter as a way of administering chemotherapy. Two cases of breast cancer were studied and their therapeutic evolution reported. Despite the poor prognosis associated with meningeal carcinomatosis, these cases had a disease response and control for a longer period than the expected median.